President Erdogan’s Discourse on the Kurdish Issue - Ayşe İrem Aycan Özer (Vestnik MGIMO-Universiteta)
The article analyzes Turkey's changing regime of ethnicity between 2004 and 2019. Turkey is a multiethnic republic that used assimilation as the key policy in its early days to create the nation-state. The Kurds, as the most populous ethnic minority, had suffered the most. The ethnic anti-minority regime was reflected in the discourse of state officials. The ethnicity regime changed only after the Justice and Development Party came to power. The state authorities acknowledged Kurds as a distinct ethnic minority, admitted the previous human rights violations, and tried to make up for past mistakes. The article reviews the evolution of the ethnicity regime through analysis of its official discourse from initially being anti-minority and through tumultuous changes to the current inclusive one. It focuses on analyzing President Erdogan's public speeches in Diyarbakir. The main finding of the article is that when the state moved away from anti-minority policies towards the Kurds, President's discourse became more inclusive. Previous studies acknowledged the agency of the state as the determining power behind changing the regime of ethnicity. The second significant contribution of this study is that organized minority groups have an independent agency; their actions significantly contributed to changing the regime of ethnicity.